1992
DOI: 10.1007/bf00587555
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of cDNA clones encodingcdc2 homologues fromOryza sativa: a functional homologue and cognate variants

Abstract: Using probes obtained by PCR amplification, we have isolated two cognate rice cDNAs (cdc2Os-1 and cdc2Os-2) encoding structural homologues of the cdc2+/CDC28 (cdc2) protein kinase from a cDNA library prepared from cultured rice cells. Comparison of the deduced amino acid sequences of cdc2Os-1 and cdc2Os-2 showed that they are 83% identical. They are 62% identical to CDC28 of Saccharomyces cerevisiae and much more similar to the yeast and mammalian p34cdc2 kinases than to rice R2, a cdc2-related kinase isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…This homolog, cdc2Os-2, cannot rescue a yeast mutant arrested in the cell cycle (Hashimoto et al, 1992). Expression of cdc2Os-1, which is a functional homolog of the yeast gene, was not regulated by GA.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This homolog, cdc2Os-2, cannot rescue a yeast mutant arrested in the cell cycle (Hashimoto et al, 1992). Expression of cdc2Os-1, which is a functional homolog of the yeast gene, was not regulated by GA.…”
Section: Discussionmentioning
confidence: 96%
“…Both genes are expressed in cultured, proliferating cells, but only cdc2Os-1 can complement a temperature-sensitive CDC28 mutant of Saccharomyces cerevisiae that is blocked at the late G1 phase. This indicates different functions for the products of these two genes in regulating the cell cycle in rice (Hashimoto et al, 1992). cDNA clones encoding plant cyclin homologs have been isolated from carrot and soybean (Hata et al, 1991), Arabidopsis (Hemerly et al, 1992), alfalfa (Hirt et al, 1992) and maize (Renaudin et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Highly homologous cdc2 gene pairs (exhibiting 80 to 90% amino acid identities) have been identified from several plant species, including maize, rice, alfalfa, soybean, Antirrhinum, and pea (Colasanti et al, 1991;Hashimoto et al, 1992;Hirt et al, 1993;Mia0 et al, 1993;Fobert et al, 1994;Jacobs 1995). The two alfalfa (Medicago sativa) cdc2 homologous genes (designated cdc2MsA and cdc2MsB) display different abilities to complement yeast cdc28 mutants blocked at GI-to-S and G,-to-M phases.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy was successful for isolating theArabidopsis 3-hydroxy-3-methylglutaryl-CoA reductase gene (21,22). The mouse squalene synthase cDNA (11) was used as a probe, because we had found that plant cell-cycle-related genes were more similar to mammalian homologs than to yeast homologs (23)(24)(25)(26).…”
mentioning
confidence: 99%